(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article explores the transformative potential of online games in revolutionizing English language learning, the power of play, how online games can enhance all four language skills: listening, reading, speaking, and writing, specific game types and features that cater to each skill, practical tips for maximizing the benefits of online game-based learning, the importance of aligning games with individual goals.